Padmakanya Multiple Campus: A Psychosocial Analysis of a First Women’s Campus in Nepal (Voice of Teacher, 2025)
Padmakanya Multiple Campus (PKMC) is oldest all-female institution in Nepal and was examined to better understand the impact of the ‘female-only’ (single-gender) learning environment on identity development, empowerment, social connection, and stress; thus, providing insights into how PKMC has influenced the students’ experiences. A phenomenological approach to data collection was followed and included collecting data from a diversity of 24 individuals (students, faculty, and staff) who attended PKMC through semi-structured interviews, focus groups, non-participant observations, and field notes. This research aimed to provide a better understanding of the psychosocial experiences of students at PKMC. The thematic analysis identified ten themes of PKMC’s psychosocial experience. These ten themes included: 1) safety and emotional freedom; 2) peer solidarity and sisterhood; 3) emerging agency and empowerment; 4) academic pressure and internalized expectations; 5) mental health struggles and stigma; 6) negotiating traditional gender norms; 7) identity exploration and career aspirations; 8) inequalities at the intersection of identities; 9) gaps in faculty support/mentoring; and 10) future orientation/social responsibility. The study found that PKMC is a safe and psychologically empowering environment for the development of leadership skills, peer support, and social engagement in the community. However, there are still issues related to school-related stress, mental health stigma, societal hierarchies, and the two identities imposed by societal expectations. Therefore, this qualitative research contributes to the current growing international and national discourse regarding women’s single-sex education with an emphasis on both the benefits of single-sex education but also the psychosocialchallenges that continue.